2006
DOI: 10.1189/jlb.1105637
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic analysis of experimental food allergen-induced cutaneous reactions

Abstract: Individuals with food allergy often present with uritcaria and atopic dermatitis. Indeed, susceptibility to food allergy may predispose to the development of these cutaneous allergic disorders. Recently, we developed a model of food allergy, whereby oral consumption of food [pea Pisum sativum L.; expressing alpha-amylase inhibitor-1 (alphaAI) from the common bean Phaseolus vulgaris L. cv Tendergreen (pea-alphaAI)] promotes a T helper cell type 2 (Th2) inflammatory response and predisposes to cutaneous allergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
0
9
4
Order By: Relevance
“…Moreover, the binding of IgE and OVA on mast cells and eosinophils was detected outside blood vessels. However, there was no infiltration of CLA + lymphocytes, which were characteristically seen in late hypersensitivity reaction and CD4 + T lymphocytes are thought to regulate eosinophil recruitment to the site of allergic skin reaction through the activity of Th2 cytokines (Prescott et al. 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the binding of IgE and OVA on mast cells and eosinophils was detected outside blood vessels. However, there was no infiltration of CLA + lymphocytes, which were characteristically seen in late hypersensitivity reaction and CD4 + T lymphocytes are thought to regulate eosinophil recruitment to the site of allergic skin reaction through the activity of Th2 cytokines (Prescott et al. 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the mechanisms which lead to the development of systemic element, and particularly the mechanisms of distant manifestations after a local allergic reaction have not been elucidated (Togias 2004). Possibilities of the development of cutaneous lesions in humans with food and milk allergy include locally and systemically produced cytokines, chemokines and several chemical mediators (Prescott et al. 2006).…”
mentioning
confidence: 99%
“…Our results are at odds with the previous study in which mice developed allergic responses to αAI peas but not to beans [8], [16]. It is possible that the source of the mice and their normal baseline diets may play a role.…”
Section: Resultscontrasting
confidence: 99%
“…42 Several studies have found increased levels of the Th2-associated cytokines IL-4, IL-5 and IL-13 in food allergic patients and mouse models of food allergy. 8589 Additionally, mutations in IL-4 Receptor A ( IL-4RA ) and IL-13 are associated with increased risk of food allergy, highlighting the importance of Th2 cytokine signaling in food allergy. 90, 91 Blockade of IL-4 and IL-13 signaling with the anti-IL-4Rα antibody dupilumab, successfully improved the clinical symptoms of subjects with asthma or atopic dermatitis, though other therapies blocking IL-4, IL-13 or IL-5 individually have been less effective.…”
Section: Modulating Th1/th2 Imbalancementioning
confidence: 99%